Development of Okura Tourism Village Based on Sociopreneurship: A Pentahelix Approach to Sustainability and Social Inclusion - Putri, Risky Arya; Andini, Frini Karina; Mustaqimmah, Nurul; Nurita, Riau; Adianto, Adianto; Amri, Khairul (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2026)
Tourism villages have emerged as strategic instruments for inclusive rural development by integrating cultural preservation, natural resource management, and local economic empowerment. This study examines the development of Okura Tourism Village in Pekanbaru, Indonesia, through the integration of sociopreneurship and the pentahelix governance framework. Employing a qualitative design combining a systematic literature review and field-based inquiry, the research analyzes tourism potentials, community-based enterprises, and multi-actor collaboration dynamics. Findings indicate that Okura possesses strong natural and cultural assets, including river tourism, agro-tourism, cycling trails, and Malay cultural heritage. Community-driven enterprises—such as ginger candy (ting jahe), palm-rib handicrafts, instant ginger powder, and ketupat belacan—demonstrate sociopreneurial characteristics by integrating economic and social values. However, structural constraints persist, including limited digital literacy, lack of certification, weak branding, and managerial gaps. IFAS and EFAS analyses reveal moderate internal strength (2.70) and favorable external conditions (3.10), suggesting significant growth potential if institutional weaknesses are addressed. This study proposes a Sociopreneurship–Pentahelix Model to foster sustainable and inclusive tourism village development. The research contributes to the discourse on community-based tourism governance by offering an integrated and replicable framework for rural innovation.